Gender Divide: Motivation and Achievement in Online English Learning - Wa Ode Restu Astuty; Sartiah Yusran; Kamaluddin Kamaluddin (Journal of Language Education and Educational Technology (JLEET), 2023)
This quasi-experimental study examined the impact of online English learning on achievement and motivation for Grade 11 students, comparing it to traditional classroom methods. Seventy-two students from SMA 2 Raha participated, with the experimental group undergoing online learning while the control group followed traditional methods. Pre- and post-tests revealed a significant improvement in the online group's achievement (p < 0.05), with a higher average gain score compared to the control group. Notably, within the online group, females showed a slightly higher average gain score (33.42) than males (27.37), indicating a gender difference. Motivation, assessed via questionnaires, indicated higher reported motivation among females (80.3%) compared to males (72.2%) in the online environment. These findings highlight the effectiveness of online English learning in enhancing overall student achievement, with females potentially experiencing a slight advantage in both achievement and reported motivation in this specific context.